2014
DOI: 10.15197/sabad.1.11.76
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Utilization of Health Services: A Hospital-Based Study in Mansoura University, Egypt

Abstract: This study aims to describe the patterns of morbidity, investigations and drug prescription among patients of Students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In the case of IPD incidence, digestive diseases, injury and poisoning, and musculoskeletal diseases were the top-ranking diagnoses for both sexes. These results show a close correlation to those in a study from Egypt [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the case of IPD incidence, digestive diseases, injury and poisoning, and musculoskeletal diseases were the top-ranking diagnoses for both sexes. These results show a close correlation to those in a study from Egypt [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…That study noted that about 42.5% of the students reported that they had used the university health center services [25]. However, the need for hospitalization was low (less than 2%), a finding equivalent to a prior hospital-based study in Egypt [26].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This study focused on the factors that influenced students' attitudes towards the services provided at the student health centre [22]. El-Gilany, El-Masry and Badwy investigated students' utilisation of health services at the Mansoura University in Egypt [23]. The main focus was on patterns of morbidity and drug prescription among patients.…”
Section: Introductionmentioning
confidence: 99%